Mediation in shareholder divorce disputes in closely held companies in Serbia - Tomić Ljubica (Pravni Zapisi)
The author analyzes disputes regarding shares in closely held companies, when couples are going through divorce. The Serbian legal framework does not provide regulations specifically for the addressed matter and the court practice is inadequate. This type of dispute is accompanied by risks to the existence of companies and the families, if not resolved in a timely manner. Mediation is generally applicable, whereby each particular case requires the assessment of mediation applicability criteria, such as gender and other sources of imbalance between the spouses. Mediation shows advantages in terms of time, confidentiality, the possibility of simultaneous resolution of multiple disputes, high voluntary fulfilment rate, and the possible improvement of relations between the parties. The inclusion of mediation clauses in shareholder agreements and in marital agreements is recommended.